2008
DOI: 10.1177/0022466907310370
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Self-Regulated Strategy Development on the Writing Performance of Second-Grade Students With Behavioral and Writing Difficulties

Abstract: The effects of a secondary academic intervention, embedded in the context of a positive behavior support model, on the writing of second-grade students at risk for emotional and behavioral disorder and writing problems were examined in this study. Students were taught how to plan and draft a story using the self-regulated strategy development model. Results of this multiple-probe design revealed lasting improvements in story completeness, length, and quality for all 6 students. Students and teachers rated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
113
1
8

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(133 citation statements)
references
References 46 publications
11
113
1
8
Order By: Relevance
“…They found that the students who receive SRSD model for POW and TREE have greater gains in essay quality when compared to students who receive traditional writing instruction. In line with Baghbadorani&Roohani (2014), Lane, Harris, Graham, Weisenbach, Brindle &Morphy (2006) also conducted the study in the same topic. Their result of their study showed that there were some improvements in story completeness, length, and quality of writing.…”
Section: Results and Analysismentioning
confidence: 77%
“…They found that the students who receive SRSD model for POW and TREE have greater gains in essay quality when compared to students who receive traditional writing instruction. In line with Baghbadorani&Roohani (2014), Lane, Harris, Graham, Weisenbach, Brindle &Morphy (2006) also conducted the study in the same topic. Their result of their study showed that there were some improvements in story completeness, length, and quality of writing.…”
Section: Results and Analysismentioning
confidence: 77%
“…many students in the classroom, some students need additional systematic instruction in writing in order to be successful (Graham, Harris & Mason, 2008). For students who are socio-economically at risk and/or are disabled, the complex processes (Lane, Harris, Graham, Weisenbach, Brindle, Morphy (2008). There is a strong body of high-quality research, however, which supports quality instruction, including writing instruction.…”
Section: Process Writingmentioning
confidence: 99%
“…In addition, surprisingly, revision of meaning related issues and formal issues seem to go hand in hand, instead of one inhibiting the other because of working memory constraints (cf. McCutchen, 2008).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Comments of peers can also help focusing on specific problems in texts, and solving these problems by suggesting concrete revisions. Such revisions can contribute to text coherence (McCutchen, 2008). A number of studies (Beal, 1996;Beason, 1993;Fitzgerald, 1987; documented that young writers find it difficult to make sensible revisions on their own.…”
Section: Writing With Peer Responsementioning
confidence: 99%